Media and law : between free speech and censorship - Deflem, Mathieu; Silva, Derek M. D. (Sociology of crime, law and deviance, 2021)
In Media and Law: Between Free Speech and Censorship, Mathieu Deflem and Derek M.D Silva have gathered an interdisciplinary team of leading experts to make a valuable contribution to the existing literature. This volume explores free speech and the control thereof from both a political as well as cultural lens. These topics have once again moved center stage in scholarly as well as popular discussions on what must, should, and should not be said in the public sphere of ideas, opinions, and tastes. In a world of alternative facts, fake news, gender politics, company self-censorship, edited art, hate speech, and career-ending tweets, the chapters in this volume make a timely contribution.